Approaches to Trademark Infrigenment in ASEAN Countries: Anaylisis of How the Case is Likely to be Deciden in Indonesia - Noerhadi, Cita Citrawinda (UI Scholars Hub, 2012)
The purpose of the establishment of the Commercial Court is to resolve civil disputes in the field of Intellectual Property Rights (IPR). Settlement of civil disputes to the Commercial Court by special judges are expected to resolve disputes in a timely manner with high fixed honor law enforcement and to be fair and can meet the expectations of society. This paper would describe the Indonesia trademark law and discuss how the courts in Indonesia is likely to decide on the facts of three landmark cases, namely Whirlpool vs Kenwood; L’Oreal SA vs Bellure NV; and Och Ziff Management Europe Limited vs OCH Capital LIP which will focus on trademark owners perception of IPR infringement in Indonesia.